2021
DOI: 10.3390/biomedicines9101453
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Photodynamic Therapy for Glioblastoma with the Mitochondria-Targeted Photosensitizer Tetramethylrhodamine Methyl Ester (TMRM)

Abstract: One of the most challenging problems in the treatment of glioblastoma (GBM) is the highly infiltrative nature of the disease. Infiltrating cells that are non-resectable are left behind after debulking surgeries and become a source of regrowth and recurrence. To prevent tumor recurrence and increase patient survival, it is necessary to cleanse the adjacent tissue from GBM infiltrates. This requires an innovative local approach. One such approach is that of photodynamic therapy (PDT) which uses specific light-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…For example, the membrane potential of mitochondria is vital to maintaining respiratory chain reactions, ion transfer, and other bioactivities. Several commercial probes, including TMRM and JC-1, have been widely applied to detect the mitochondria membrane potential [ 78 , 79 ]. Chemical reagents are also important for the normal activity of mitochondria.…”
Section: Design Of Molecular Probes For Organelle-targeted Cell Imagingmentioning
confidence: 99%
“…For example, the membrane potential of mitochondria is vital to maintaining respiratory chain reactions, ion transfer, and other bioactivities. Several commercial probes, including TMRM and JC-1, have been widely applied to detect the mitochondria membrane potential [ 78 , 79 ]. Chemical reagents are also important for the normal activity of mitochondria.…”
Section: Design Of Molecular Probes For Organelle-targeted Cell Imagingmentioning
confidence: 99%
“…Organelle targeting becomes a more practical and efficient approach to minimize the reoccurrence of tumors. Vasilev et al worked on a mitochondria-targeted photosensitizer, namely tetramethylrhodamine methyl ester (TMRM), to evaluate the mitochondria capability [94]. They used a small dose of this photosensitizer approach and observed that this dye was excited by the green/yellow spectrum having better tissue penetration.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…For instance, tetramethylrhodamine methyl ester (TMRM), the least toxic of all widely used trackers for mitochondria, can only be employed at doses up to 0.5 μM without having an inhibitory effect on respiration. 17,18 Additionally, the most popular cyanine-based mitochondria-targeting probe, JC-1, can only exhibit red emission when introduced in micromolar concentrations forming J-aggregates, which results in high cytotoxicity. 19…”
mentioning
confidence: 99%
“…For instance, tetramethylrhodamine methyl ester (TMRM), the least toxic of all widely used trackers for mitochondria, can only be employed at doses up to 0.5 mM without having an inhibitory effect on respiration. 17,18 Additionally, the most popular cyanine-based mitochondria-targeting probe, JC-1, can only exhibit red emission when introduced in micromolar concentrations forming J-aggregates, which results in high cytotoxicity. 19 Given the above considerations, we proposed a precisely designed non-toxic mitochondria-targetable NIR-emitting (l em E 830 nm) probe, T2, by conjugating a cationic cyaninebased dye and a HDAC6 inhibitor (Scheme 1b).…”
mentioning
confidence: 99%